PENGARUH LOKASI USAHA TERHADAP KEUNTUNGAN (STUDI KASUS TOKO PAKAIAN DI KECAMATAN BANTAN KABUPATEN BENGKALIS) - Sandi Andika; Lukluil Mukarromah (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
Various factors that cause success in the business carried out by entrepreneurs, one of which is the location of the business. The right business location will certainly have a positive impact on the sustainability and profits of thebusiness. This study aims to determine the effect of business location on profits. The subjects in this study wereclothing store business owners who opened a business in Bantan District with a total of 23 shops, so theresearchers used total sampling. This type of research is field research with quantitative research methods. Data collection techniques used are observation, questionnaires or questionnaires, and documentation. Based on theresults of data analysis, it can be concluded that the correlation coefficient can be stated that there is a positive relationship between the business location variable and the profit variable which is categorized as "Low", becausethe correlation coefficient obtained is 0.246 or 24.6% smaller than r table with a significance level of 5% of 0.3515.. based on the results of regression analysis and t test results with a significance level of 0.257 > 0.05 indicatingthat Ho is accepted and Ha is rejected with the information that the location of the business has no significant effect on the profits of the clothing store business.